APLIKASI PROGRAM UKGS INOVATIF IRENE’S DONUTS TERHADAP PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT SERTA OHI-S PADA ANAK BERKEBUTUHAN KHUSUS (ABK) DI SLB NEGERI SEMARANG - Betty Saptiwi; Sukini Sukini; Salikun Salikun; Supriyana Supriyana (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEApplication of innovative UKGS program “irene’s donuts” to oral and dental health behavior and OHI-s of children with special needs in SLB Negeri SemarangABSTRACTChildren with Special Needs (CSN) are children who have abnormalities in the context of education, they should get a special care of the teeth and mouth health from both the teachers at school and the parents at home. Most elementary school CSN in The State Special Elementary School of Semarang 77% suffered from dental caries, so it needs special attention. Irene's Donuts Oral Health School Innovative Program is an innovation program using Irene's Donut's method that have been proven in reducing the risk of caries in the elementary school, so it needs to be tested to primary level CSN The State Special Elementary School of Semarang.The type of this research is a quasi experimental study with a non-randomized pretest-posttest equivalent control group design. This study was conducted on 76 respondents. There were 38 respondents in the control group and 38 respondents in the experimental group.The Pre and Post Test result of Dependent T Test against the Oral Hygiene Index (OHI-S) shows that the p value is 0.000. The results of Mann-Whitney test on the behavior of dental and oral health care in the control group and the treatment group shows 0.024 of p value.The conclusion from this research is that there is a difference between the OHI-S before and after the application of Innovative Irene's Donuts program to the CSN in The State Special Elementary School of Semarang. Moreover, there is a difference between the behavior of the maintenance of the oral health before and after the application of the program. Key words : Oral Health School Program, Irene’s Donuts, OHI-S